Effect of Fermentation Extracts against Bemisia tabaci on Chilli Pepper (Capsicum annuum) - Rudi Putra Munandar; Suwandi Suwandi (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2021)
This experiment was aimed to determine the effects of application of fermentation extracts on the development of pepper yellow leaf curl and whitefly on chilli. Experiment arranged in a completely randomized block design with four treatments (water as control, fermentations extracts named TSNGlu, BP4, and BP4Glu). The results showed symptoms in the form of curling of young leaves. The color of the leaves was relatively green. Yellow symptoms commonly found when severe were not found in the experiment. The symptoms of severe disease are marked in yellow at the top of the leaf and remain green at the bottom. The laboratory used 350 lux (underexposed light) so the symptoms become slight. ack of light intensity made plants etiolated and could not carry out photosynthesis properly. Each experiment consisted of 4 fermentation extract treatments. Each treatment. Overall, all treatments without fermentation and also AUDPC of the disease did not significantly affect the treatment of fermented extract both the incidence and severity of the low pepper yellow leaf curl virus. The treatment by spraying did not significantly affect the population of whitefly, except at 7 days after infestation, inversely proportional to the spraying treatment by means of discharge significantly affected from 14 days after infestation. The increase in plant height spray treatment did not have a significant effect and for spraying treatment with extraction of fermentation did not significantly affect the canopy area of ​​the plant canopy.